Direct Electrophilic Acylation of N-Substituted Pyrazoles by Anhydrides of Carboxylic Acids - Taydakov, Ilya V.; Krasnoselskiy, Sergey S. (Synthesis, 2013)
A simple, convenient and scalable approach to 1-substituted 4-acylpyrazoles through direct acylation of pyrazoles by anhydrides of aliphatic, aromatic and fluorinated carboxylic acids in the presence of concentrated sulfuric acid as a catalyst is described. Target ketones were obtained in 41–86% isolated yields in high purity without laborious purification. The scope and limitations of the method are discussed.
Keywords: electrophilic aromatic acylation; heterocycles; ketones; catalysis